2019
DOI: 10.1007/s12208-019-00218-2
|View full text |Cite
|
Sign up to set email alerts
|

Eating styles of young females in Azerbaijan

Abstract: An epidemic of twenty-first century is overweight and obesity which is a consequence of inappropriate eating habits and sedentary lifestyle. Relying on statistical data overweight and obesity is a serious problem for young people, since the ratio of obese young people (below 35) is constantly increasing in the developed regions of the world. In an empirical research 419 adult females between 24 and 38 were questioned. The aim of the research was to segment Azerbaijan females belonging to Generation Y based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The Food-Related Lifestyle instrument used in two studies [36,43] did not produce similar findings, except one segment from each that were indifferent to food-related lifestyle factors. The most similar outcomes between studies were those using the TFEQ for segmentation (n = 3) [27,38]. Despite having a different number of segments generated from cluster analysis, the three studies using the TFEQ all found a segment with a low tendency to emotionally eat-the 'rational' segment (in two studies) [27] and the 'conscious' segment [38].…”
Section: Outcomes Of Segmentationmentioning
confidence: 85%
See 4 more Smart Citations
“…The Food-Related Lifestyle instrument used in two studies [36,43] did not produce similar findings, except one segment from each that were indifferent to food-related lifestyle factors. The most similar outcomes between studies were those using the TFEQ for segmentation (n = 3) [27,38]. Despite having a different number of segments generated from cluster analysis, the three studies using the TFEQ all found a segment with a low tendency to emotionally eat-the 'rational' segment (in two studies) [27] and the 'conscious' segment [38].…”
Section: Outcomes Of Segmentationmentioning
confidence: 85%
“…Study populations ranged from n = 73 to n = 3085 participants aged between 18 years and 85+ years. The majority of studies included both male and female participants (n = 28) [13,[26][27][28][32][33][34][35][36][37][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54], however one had females only [38], and one did not specify sex or gender [43]. The studies included were from a range of countries such as Australia (n = 4) [13,33,47,54], Chile (n = 3) [48][49][50], and Croatia (n = 2) [32,42], and were published in a range of journals from public health, nutrition, and social marketing disciplines.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations